“Tree Is Life”: The Rising of Dualism and the Declining of Mutualism among the Gedeo of Southern Ethiopia - Regassa Debelo, Asebe; Legesse, Abiyot; Milstein, Tema; Orkaydo, Ongaye Oda (Frontiers in Communication, 2017)
This study investigates ecocultural discourses and practices among the Gedeo in southern Ethiopia within the contexts of globalizing commodification of nature, successive governmental extractivist and conservationist discourses, and increasingly influential colonial present religious systems. Our analysis illustrates ways in which indigenous Gedeo understandings of reciprocal ecological coexistence are rooted in cultural knowledge, values, and customs. However, competing forms of knowledge introduced in the form of governance, commerce, conservation, and religion have resulted in an in-process shift from traditionally spiritually maintained mutualist human-environment relations to dualist commodified relations, particularly among youth, and dualist expert-reliant conservationist relations emanating from governmental bodies. By examining a traditional meaning system during an explicit process of erasure, the study points to ways local meanings of, and narratives about, ecocultural interactions are produced and communicated within wider contexts of power, and illustrates tensions among traditional, governmental, capitalist, conservationist, and religious environmental ontologies in everyday and institutional practice.